ESG DISCLOSURE AND PROFITABILITY: IS THE RELATIONSHIP TOO GOOD TO BE TRUE FOR ALL FIRMS? - Muhammad Miftahuddin; Widad Nabila Azzahra; Kumaralalita Makusara; Irene Rini Demi Pangestuti; Hisyam Kholish Prabaswara; Danes Quirira Octavio (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2026)
Introduction: This study aims to investigate the effect of Environmental, Social, and Governance Disclosure Score on firm profitability in ASEAN and explain the effect of ESGD on companies of different sizes. Methods: This quantitative study was conducted from 2019 to 2023 with 264 non-financial companies selected based on purposive sampling and resulting in 1,320 observations. This study uses panel data regression analysis and is supplemented with a robustness test: NPM (Net Profit Margin) as alternative proxy for profitability and sample split based on firm size. Results: Our research shows that ESGD, ENVD, and SOCD have significant positive effect on profitability in all models, including robustness tests. However, our research shows inconsistent relationship with the GOVD. Additional analysis shows that in large companies, ESGD and its dimensions consistently have significant positive effect on profitability. Otherwise, in small companies ESGD and its dimensions do not show statistical significance. Conclusion and suggestion: Our findings emphasize the importance of implementing ESGD for large companies to increase profitability. Meanwhile, for small companies implementing ESGD is not rational due to the high cost of ESG, and they can focus on cheaper initiatives. This is especially true in emerging markets such as Southeast Asia.